Pemberdayaan Ekonomi Perempuan melalui Usaha Mikro Konveksi - Abdul Hamid (PSGA LP2M IAIN Pontianak, 2016)
To begin with, there are two alternatives for women to expand their economy through micro garment business. Firstly, self-taught learning or independently studying by undergoing the trials and collecting the information related to tailoring and screen printing skills. Secondly, learning those through the course or training institution. Through this article, furthermore, women could easily fight for their own war of financial problem of theirs.